Application of Mind Mapping Method to Interest Students' in Reading Comprehension - Chusnul Chotimah; Tauricha Astiyandha (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2019)
This research is about Application of Mind Mapping Method to Interest Students in Reading Comprehension. Mind Mapping is a graphical way to represent ideas and concepts. The researcher believes that this method can make the students more interested in learning English especially in reading comprehension. This research did about six months in SMPIT Yapidh, Jati Asih, Bekasi in academic year 2018- 2019. The participants in this research are all students on ninth grade, as a sample the researcher chose the students at IX E classroom, there were 25 students and all of them are females. The method of this research is descriptive qualitative. The instruments that used in this research are interview and observation. And based the data, the researcher can conclude that mind mapping method can make the students more interested in learning English. The result of this research shows that, 1) All students can make a mind mapping based on the story, 2) Application mind mapping method makes the learning process funny and easily, 3) Learning reading comprehension more simple.